Composição química e atividade antioxidante dos óleos essenciais das folhas de Eugenia patrisii Vahl, E. punicifolia (Kunth) DC., E Myrcia tomentosa (Aubl.) DC., MYRTACEAE. - FRANCO, Celeste de Jesus Pereira (2023)
Eugenia L. and Myrcia DC. are the most representative genera of the Myrtaceae family. The species of these genera are used in traditional medicine and others are appreciated for their edible fruits. In addition, they are essential oils sources with great antioxidant, anticancer, phytotoxic and antimicrobial potential. The aim of this work was to evaluate the chemical composition and antioxidant activity of essential oils from the leaves of Eugenia patrisii, E. punicifolia and Myrcia tomentosa. Essential oils (EOs) were extracted from Eugenia patrisii, E. punicifolia, and Myrcia tomentosa, specimens A and B, using hydrodistillation. Gas chromatography coupled with mass spectrometry (GC/MS) was used to identify the volatile constituents present, and the antioxidant capacity of EOs was determined using diphenylpicryl-hydrazyl (DPPH) and trolox equivalent antioxidant capacity (TEAC) assays. For E. patrisii, germacrene D (20.03%), bicyclogermacrene (11.82%), and (E)-caryophyllene (11.04%) were identified as the major constituents of the EOs extracted from specimen A, whereas specimen B primarily comprised γ-elemene (25.89%), germacrene B (8.11%), and (E)-caryophyllene (10.76%). The EOs of E. punicifolia specimen A contained β-Elemene (25.12%), (E)-caryophyllene (13.11%), and bicyclogermacrene (9.88%), while specimen B was composed of (E)-caryophyllene (11.47%), bicyclogermacrene (5.86%), β-pinene (5.86%), and γ-muurolene (5.55%). The specimen A of M. tomentosa was characterized by γelemene (12.52%), germacrene D (11.45%), and (E)-caryophyllene (10.22%), while specimen B contained spathulenol (40.70%), α-zingiberene (9.58%), and γ-elemene (6.89%). Additionally, the chemical composition of the EOs was qualitatively and quantitatively affected by the collection period. Furthermore, the EOs of the studied specimens, especially specimen A of E. punicifolia, showed a greater antioxidant activity in DPPH rather than TEAC, as represented by a significantly high inhibition percentage (408.0%).